Innovations in the management of epistaxis secondary to hereditary hemorrhagic telangiectasia: our evolution to injection sclerotherapy as the treatment of choice - Kumar, Nitish; Lança Gomes, Pedro; Marino, Michael J.; Miglani, Amar; Lal, Devyani (Frontiers in Allergy, 2024)
IntroductionWe compared the efficacy of intralesional sclerotherapy using 3% sodium tetradecyl sulfate with non-sclerotherapy-based treatments for Hereditary Hemorrhagic Telangiectasia-associated epistaxis management.MethodologyThis is a retrospective study of patients who underwent surgical intervention for HHT-associated epistaxis management from 01/2010–02/2024. Patients undergoing sclerotherapy with intralesional 3% sodium tetradecyl sulfate were included in the sclerotherapy group and others undergoing conventional non-sclerotherapy-based procedures in the non-sclerotherapy group. Outcomes like breakthrough epistaxis, emergency visits, intra-op blood loss, blood transfusions, and procedure complications in the 3-month perioperative period were compared.ResultsTwenty-three patients who underwent 74 intranasal procedures were identified. In the sclerotherapy group, 17 patients underwent 47 procedures. In the non-sclerotherapy group, 10 patients underwent 27 procedures. Till the 3rd post-treatment month, fewer breakthrough epistaxis episodes were observed after sclerotherapy procedures (13/47) vs. non-sclerotherapy procedures (14/27); (p = 0.037). Intraoperative blood loss was significantly lower during sclerotherapy (median: 10 ml) vs. non-sclerotherapy procedures (median: 50 ml); p < 0.001. The time interval between successive procedures was not significantly different in the sclerotherapy (median 6.5 months) vs. the non-sclerotherapy group (median 3.5 months); p = 0.13. Nasal crusting was the most common complication in the sclerotherapy group (36.9%). Two patients in each group had new onset septal perforation, none of the patients had vision loss or cerebrovascular accident. One emergency department visit was reported in the sclerotherapy group vs. 7 (in 3 patients) in the non-sclerotherapy group.ConclusionsCompared to non-sclerotherapy treatments, intralesional sclerotherapy for epistaxis in HHT is more effective in decreasing breakthrough epistaxis, and has lower intraoperative blood loss.